Transcriptomic identification of key genes in Pacific oysters Crassostrea gigas responding to major abiotic and biotic stressors. Issue 131 (December 2022) - Liu, Youli; Bao, Zhenmin; Lin, Zhihua; Xue, Qinggang
Abstract: Oysters are commercially important intertidal filter-feeding species. Mass mortality events of oysters often occur due to environmental stresses, such as exposure to fluctuating temperatures, salinity, and air, as well as to metal pollution and pathogen infection. Here, RNA-seq data were used to identify shared and specific responsive genes by differential gene expression analysis and weighted gene co-expression network analysis. A total of 18 up-regulated and 10 down-regulated shared responsive genes were identified corresponding to five different stressors. Total 27 stressor-specific genes for temperature, 11 for salinity, 80 for air exposure, 51 for metal pollution, and 636 for Vibrio mediterranei pathogen stress were identified in oysters. Elongin-β was identified as a crucial gene for thermal stress response. Some HSP70s were determined to be shared responsive genes while others were specific to thermal tolerance. The proteins encoded by these stress-related genes should be further investigated to characterize their physiological functions. In addition, the uncharacterized proteins and ncRNAs that were identified may be involved in species-specific stress-response and regulatory mechanisms. This study identified specific genes related to stressors relevant to oyster cultivation. These findings provide useful information for new selective breeding strategies using a data driven method. Graphical abstract: Image 1 Highlights: Pacific oysters are exposed to various biotic and abiotic stressors. Key environmental stress-responsive genes in oysters were investigated. Differentially regulated genes specific to stressors were identified. Such genes could be used as biomarkers for monitoring and breeding oyster.